Art in theory 1815-1900: an anthology of changing ideas - Harrison, Charles; Wood, Paul; Gaiger, Jason (Oxford Blackwell, 1998)
Art in Theory (1648-1815) provides a wide-ranging and comprehensive collection of documents on the theory of art from the founding of the French Academy until the end of the Napoleonic Wars. Like its highly successful companion volumes, Art in Theory (1815-1900) and Art in Theory (1900-1990), its' primary aim is to provide students and teachers with the documentary material for informed and up-to-date study. Its' 240 texts, clear principles of organization.